BPIFA1 regulates lung neutrophil recruitment and interferon signaling during acute inflammation - Britto, Clemente J. (Am J Physiol Lung Cell Mol Physiol, 2019)
Bpifa1 (BPI fold-containing group A member 1) is an airway host-protective protein with immunomodulatory properties that binds to LPS and is regulated by infectious and inflammatory signals. Differential expression of Bpifa1 has been widely reported in lung disease, yet the biological significance of this observation is unclear. We sought to understand the role of Bpifa1 fluctuations in modulating lung inflammation. We treated wild-type (WT) and Bpifa1(−/−) mice with intranasal LPS and performed immunological and transcriptomic analyses of lung tissue to determine the immune effects of Bpifa1 deficiency. We show that neutrophil (polymorphonuclear cells, PMNs) lung recruitment and transmigration to the airways in response to LPS is impaired in Bpifa1(−/−) mice. Transcriptomic analysis revealed a signature of 379 genes that differentiated Bpifa1(−/−) from WT mice. During acute lung inflammation, the most downregulated genes in Bpifa1(−/−) mice were Cxcl9 and Cxcl10. Bpifa1(−/−) mice had lower bronchoalveolar lavage concentrations of C-X-C motif chemokine ligand 10 (Cxcl10) and Cxcl9, interferon-inducible PMN chemokines. This was consistent with lower expression of IFNγ, IFNλ, downstream IFN-stimulated genes, and IFN-regulatory factors, which are important for the innate immune response. Administration of Cxcl10 before LPS treatment restored the inflammatory response in Bpifa1(−/−) mice. Our results identify a novel role for Bpifa1 in the regulation of Cxcl10-mediated PMN recruitment to the lungs via IFNγ and -λ signaling during acute inflammation.